Research on XRII Image Distortion Correction Based on Biharmonic Spline Surface Interpolation (Journal of Fiber Bioengineering and Informatics, 2015)
X-Ray Image Intensifier (XRII) suffers from serve distortion in C-arm CT imaging system. To overcome\rthe challenging problem, this paper proposes a novel XRII correction based on the Biharmonic Spline\rSurface Interpolation (BSSI) framework. In our study, two functions X_2 =f(X_1, Y_1) and Y_2 =f(X_1, Y_1)\rare first developed to map the relation between pixels positions in the distorted XRII image and reference\rimage. A bilinear interpolation can then be applied to estimate the corrected pixel intensities to\rachieve the final image. The proposed approach can well overcome the discontinuities problems in local\ralgorithms and achieve improved accuracy in distortion correction. Experiment results demonstrate\rthat the proposed algorithm is capable of providing XRII images with higher correction precision than\rclassical algorithms.
Keywords: C-arm CT; XRII Image; Biharmonic Spline Surface Interpolation (BSSI); Distortion Correction; Correction Precision